Quantitative Analysis of Cellular Proteome Alterations in CDV-Infected Mink Lung Epithelial Cells - Tong, Mingwei; Yi, Li; Sun, Na; Cheng, Yuening; Cao, Zhigang; Wang, Jianke; Li, Shuang; Lin, Peng; Sun, Yaru; Cheng, Shipeng (Frontiers in Microbiology, 2017)
Canine distemper virus (CDV), a paramyxovirus, causes a severe highly contagious lethal disease in carnivores, such as mink. Mink lung epithelial cells (Mv.1.Lu cells) are sensitive to CDV infection and are homologous to the natural host system of mink. The current study analyzed the response of Mv.1.Lu cells to CDV infection by iTRAQ combined with LC–MS/MS. In total, 151 and 369 differentially expressed proteins (DEPs) were markedly up-regulated or down-regulated, respectively. 13 DEPs were validated via real-time RT-PCR or western blot analysis. Network and KEGG pathway analyses revealed several regulated proteins associated with the NF-κB signaling pathway. Further validation was performed by western blot analysis and immunofluorescence assay, which demonstrated that different CDV strains induced NF-κB P65 phosphorylation and nuclear translocation. Moreover, the results provided interesting information that some identified DEPs possibly associated with the pathogenesis and the immune response upon CDV infection. This study is the first overview of the responses to CDV infection in Mv.1.Lu cells, and the findings will help to analyze further aspects of the molecular mechanisms involved in viral pathogenesis and the immune responses upon CDV infection.